Mortality and major cardiovascular events among patients with multiple myeloma: analysis from a nationwide French medical information database. (14th October 2021) - Cottin, Y; Boulin, M; Doisy, C; Mounier, M; Caillot, D; Chretien, M L; Bodin, A; Herbert, J; Bonnotte, B; Zeller, M; Maynadie, M; Fauchier, L
Abstract: Background: Cardiovascular disease (CVD) in patients with multiple myeloma (MM) may derive from multiple factors unrelated to the disease (age, diabetes, dyslipidemia, obesity, prior CV diseases), related to the disease and/or related to antimyeloma treatment. Based on a nationwide hospitalization database, we aimed to assess the risk of all-cause death, and CV outcomes in MM patients. Methods: From 1st January 2013 to 31st December 2013, 3, 381, 472 adults (age ≥18 years) were hospitalized for any reason in French hospitals and then had at least 5 years of complete follow-up (or suffered death earlier). We identified 15, 774 patients diagnosed with known MM at baseline. The outcome analysis (all-cause death, cardiovascular [CV] death, myocardial infarction (MI), ischemic stroke or hospitalization for major bleeding) was performed with follow-up starting at the time of last event. For each patient with MM, a propensity score-matched patient with no MM was selected (1:1) using the one-to-one nearest neighbor method. Findings: The mean follow-up in the propensity-score-matched population was 3.7±2.3 years, median 5.0, IQR 1.3–5.7 years. During follow-up, matched patients with MM (15 774 patients) had a higher risk of all-death (yearly rate 20.02 vs 11.39%/year) than patients without MM. No difference was observed between MM group and no myeloma group for CV death (2.00 vs 2.02%/year). The rate of MI and stroke was markedly lower in the MM group, respectively for incidence rate, 0.86 vs 0.97%/year and 0.85 vs 1.10%/year. In contrast, MM group had a higher rate of rehospitalization for major bleeding with an incidence rate of 3.61 vs 2.24%/yr and a higher risk of intracranial bleeding (1.03 vs 0.84%/yr). Results were similar in sensitivity analysis limited to patients with recent MM (i.e. diagnosed within the 3 previous months). Interpretation: From a large nationwide database, we show that although patients with MM are not at higher risk of CV death, they had a higher risk of mortality due to major bleeding and intracranial bleeding. Our findings highlight the key issue of anticoagulation treatment management in patients with MM. Funding Acknowledgement: Type of funding sources: None.